Assessment of Psychological Distress in Health Care Workers During the First two Waves of COVID-19: A Follow-up of a Canadian Longitudinal Study. (June 2022) - Dufour, Marie-Michèle; Bergeron, Nicolas; Guay, Stéphane; Geoffrion, Steve
Background: Health care workers (HCW) exposed to COVID-19 risk experiencing psychological distress. Little is known regarding longitudinal perspectives and evolutions of psychological distress within this population. The objective of this study is to extend the results of our previous study to the pandemic's second wave. Method: This prospective cohort study was conducted from May 8, 2020, to January 24, 2021, and includes 787 HCW. Symptoms of anxiety and depression were assessed using the Generalised Anxiety Disorder-7 (GAD-7) and the Patient Health Questionnaire-9 (PHQ-9). Descriptive statistics illustrated the evolution of psychological distress indicators, whereas latent class analysis helped identify trajectories. Results: The results showed that a lower proportion of HCW exceeded the clinical threshold during the second wave (36, 5% vs. 31, 1%). As in the first wave, most of our sample fell onto the resilient trajectory (67.22%). We adapted the name of the remaining trajectories to better suit their evolution: rapid recovery (15.76%), slow recovery (9.66%), and delayed (7.37%). Conclusion: Approximately two-thirds of the HCW did not manifest significant distress. For those who did, the distress was transient. We observed a trend of positive adaptability among HCW, considering that the proportion of HCW experiencing psychological distress exceeding clinical threshold remained lower than during the first wave. Our data highlight the dynamic nature of psychological distress. To be able to detect psychological distress as it arises, HCW should use self-monitoring as an essential tool. This vigilance would allow institutions to offer timely support and resources for those experiencing psychological distress.